2015
DOI: 10.1159/000371769
|View full text |Cite
|
Sign up to set email alerts
|

Spot Check Analysis of Gas Exchange: Invasive versus Noninvasive Methods

Abstract: Background: Correct measurement of PO2 and PCO2 is essential to establish appropriate therapy such as long-term oxygen therapy (LTOT) in patients suffering from respiratory failure. Objectives: We aimed to compare common invasive and noninvasive methods for assessing blood gas components for spot check analysis. Methods: Arterial (PaO2, PaCO2) and capillary blood gas (PCBGO2, PCBGCO2) measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 26 publications
0
36
2
4
Order By: Relevance
“…1,2,[5][6][7] Different trials have evaluated the agreement between ABG and CBG in terms of PO 2 measurements, with conflicting results; whereas one trial reported close agreement between ABG-versus CBG-derived values over a wide range of PO 2 values, 7 other trials showed wide limits of agreement (LOA). 8,9 A 2007 meta-analysis comparing ABGs to CBGs emphasized that capillary PO 2 (P c O 2 ) (earlobe sampling) may be an appropriate replacement for arterial PO 2 (P a O 2 ); 2 however, the authors also pointed out that CBG might not be appropriate if precision is required, based on the fact that the residual standard error (SE) in the regression equation was 6 mmHg. 2 This is of great importance, since, for example, long-term oxygen therapy (LTOT) is based on absolute values of PO 2 .…”
mentioning
confidence: 99%
“…1,2,[5][6][7] Different trials have evaluated the agreement between ABG and CBG in terms of PO 2 measurements, with conflicting results; whereas one trial reported close agreement between ABG-versus CBG-derived values over a wide range of PO 2 values, 7 other trials showed wide limits of agreement (LOA). 8,9 A 2007 meta-analysis comparing ABGs to CBGs emphasized that capillary PO 2 (P c O 2 ) (earlobe sampling) may be an appropriate replacement for arterial PO 2 (P a O 2 ); 2 however, the authors also pointed out that CBG might not be appropriate if precision is required, based on the fact that the residual standard error (SE) in the regression equation was 6 mmHg. 2 This is of great importance, since, for example, long-term oxygen therapy (LTOT) is based on absolute values of PO 2 .…”
mentioning
confidence: 99%
“…Although transcutaneous oxygen (PtO 2 ) was monitored in our study (14), SpO 2 assessment has been found to be at least more favourable than PtO 2 as a non-invasive method to analyse blood oxygenation (14). Additionally, we can say that SpO 2 is more important than PaO 2 regarding the effect on oxygen delivery to tissues (14). Mir et al (12) did not report any systematic SpO 2 value during the procedure.…”
Section: Discussionmentioning
confidence: 67%
“…Measurements of pre-oxygenation have focused on EtO 2 of >90% because this is the most readily measurable, whereas a more accurate measure of the efficacy of pre-oxygenation is the arterial oxygen partial pressure. Although transcutaneous oxygen (PtO 2 ) was monitored in our study (14), SpO 2 assessment has been found to be at least more favourable than PtO 2 as a non-invasive method to analyse blood oxygenation (14). Additionally, we can say that SpO 2 is more important than PaO 2 regarding the effect on oxygen delivery to tissues (14).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations